Analysis of pectin biopolymer phase states using acoustic emissions - Zheng, Yifan; Wagner, Willi Linus (Carbohydrate polymers, 2020)
Acoustic emissions are stress or elastic waves produced by a material under external load. Since acoustic emissions are generated from within and transmitted through the substance, the acoustic signature provides insights into the physical and mechanical properties of the material. In this report, we used a constant velocity probe with force and acoustic emission monitoring to investigate the properties of glass phase and gel phase pectin films. In the gel phase films, a constant velocity uniaxial load produced periodic premonitory acoustic emissions with coincident force variations (saw-tooth pattern). SEM images of the gel phase microarchitecture indicated the presence of slip planes. In contrast, the glass phase films demonstrated early acoustic emissions, but effectively no force or acoustic evidence of periodic or premonitory emissions. Microstructural imaging of the glass phase films indicated the presence of early microcracks as well as dense polymerization of the pectin (without evidence of slip planes). We conclude that the water content in the pectin films contributes to not only the physical properties of the films, but also the stick-slip motion observed with constant uniaxial load. Further, acoustic emissions provide a sensitive and practical measure of this mechanical behavior.